South Korea's missile forces and the emergence of triangular strategic (in)stability. Issue 1 (2nd January 2020) - Pollack, Joshua H.; Kim, Minji
ABSTRACT: South Korea's sustained pursuit of conventional precision-strike capabilities and greater autonomy in military decision making is reshaping strategic-stability dynamics between its nuclear-armed ally, the United States, and its nuclear-armed adversary, North Korea. For the last decade, advances in conventional, precision-strike missiles in both Koreas have accompanied reciprocal threats of pre-emption and attacks on leaders, creating a new pathway for a crisis to escalate into a war. Given US security guarantees to South Korea, and North Korea's development of a nuclear arsenal to deter the United States, any large-scale armed conflict in Korea is liable to involve the use of nuclear weapons. The traditional concern of the alliance with the quality of extended deterrence should be broadened to reflect an understanding of this triangular stability dynamic.